The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1108/ijshe-06-2021-0243
|View full text |Cite
|
Sign up to set email alerts
|

Towards meta–competences in higher education for tackling complex real–world problems – a cross disciplinary review

Abstract: Purpose Climate change, poverty and pandemics are some of the complex real-world problems that are increasingly challenging higher education institutions (HEIs) to equip future graduates with meta-competences that have hitherto not been demanded. These graduates need to be able to capture and operate within complex systems and relationships. By focusing on complex real-world problems, this study aims to systematically review competences and frame meta-competences supporting curricula development in HEIs. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…The path to a more sustainable world will depend on developing the competencies of the planet’s future citizens (Bali and Yang-Wallentin, 2020; Rieckmann et al , 2017). Previous studies have shown that although complex real-world problems can be addressed more sustainably through the development of common meta-competencies, it is necessary to specify to what extent each competence can address a specific sustainability problem in the real world ( Bates et al ., 2022). ESD is based on this assertion, and, to this end, a series of competencies have been presented that are considered essential for students if they are to contribute to the SDGs.…”
Section: Competencies That Define Physical Education For Sustainable ...mentioning
confidence: 99%
“…The path to a more sustainable world will depend on developing the competencies of the planet’s future citizens (Bali and Yang-Wallentin, 2020; Rieckmann et al , 2017). Previous studies have shown that although complex real-world problems can be addressed more sustainably through the development of common meta-competencies, it is necessary to specify to what extent each competence can address a specific sustainability problem in the real world ( Bates et al ., 2022). ESD is based on this assertion, and, to this end, a series of competencies have been presented that are considered essential for students if they are to contribute to the SDGs.…”
Section: Competencies That Define Physical Education For Sustainable ...mentioning
confidence: 99%